Lung abscess from Staphylococcus aureus after varicella infection in a 3-month-old infant - Deniz Aygun; Fatih Aygun; Ayse A. Kılınc; Halit Cam; Haluk Cokugras; Yıldız Camcıoglu (Elsevier, 2017)
Varicella is a common, highly contagious viral infection of childhood. Varicella is a usually benign and self-limited disease, but it can be complicated by severe bacterial infections, especially in immunocompromised hosts. In this study, we describe a previously healthy 3-months-old infant who was admitted with high fever, cough, and respiratory distress, who had a history of varicella infection three weeks before, with exposure from her adolescent, unvaccinated sister. A lung abscess caused by Staphylococcus aureus complicating the varicella infection was discovered. The patient was aggressively treated with drainage of the abscess and intravenous antibiotics and had a good recovery. Keywords: Varicella, Lung abscess, Infant